Strategic Pathways to Healthcare Excellence: A Review of Innovative Approaches for Improving Medical Services - Alkabir, Abdullah Mohammad; Alkabir, Hussein Mohammad; Al Farhan, Abdulaziz Salem; Dakam, Mansour Ahmad; Sarar, Mohammed Abdullah Hassan; Almahri, Saleh Ali Saleh; Al Gahas, Khaled Ahmed; Al-Shahi, Ali Hussein (Journal of Posthumanism, 2024)
This review article explores the strategic pathways and innovative approaches that healthcare institutions are adopting to improve medical services in the face of rising demand, technological advancement, and quality expectations. The paper synthesizes evidence from global practices to highlight strategies such as digital health integration, patient-centered care models, Lean and Six Sigma in clinical settings, workforce development, and interdepartmental collaboration. It emphasizes how innovation, policy, and leadership intersect to enhance accessibility, efficiency, and patient outcomes. The findings suggest that combining technology with management strategies creates sustainable improvements in healthcare delivery. The article concludes with implications for healthcare policymakers, practitioners, and researchers, offering recommendations for aligning strategies with national health priorities and international best practices.